Defense response of strawberry plants against Botrytis cinerea influenced by coriander extract and essential oil - Dėnė, Lina; Laužikė, Kristina; Rasiukevičiūtė, Neringa; Chrapačienė, Simona; Brazaitytė, Aušra; Viršilė, Akvilė; Vaštakaitė-Kairienė, Viktorija; Miliauskienė, Jurga; Sutulienė, Rūta; Samuolienė, Giedrė; Valiuškaitė, Alma (Frontiers in Plant Science, 2023)
Essential oils and extracts are investigated in sustainable plant protection area lately. Alternative antifungal substances are especially relevant for major economic-relevance pathogens, like Botrytis cinerea (causal agent of strawberry grey mold), control. However, the reaction of plants to alternative protection with plant-origin products is currently unknown. Induced stress in plants causes changes in antioxidant and photosynthetic systems. The aim of the research was to determine the defense response of strawberry plants under application of coriander seed products. In the first step of the research, we determined coriander seed (Coriandrum sativum), black seed (Nigella sativa) and peppermint leaf (Menta × piperita) products’ antifungal activity against B. cinerea in vitro. Secondly, we continued evaluation of antifungal activity under controlled environment on strawberry plants of the most effective coriander seed products. Additionally, we evaluated the antioxidant and photosynthetic parameters in strawberries, to examine the response of plants. Antifungal activity on strawberries was determined based on grey mold incidence and severity after application of coriander products. Impact on photosynthetic system was examined measuring photosynthetic rate, transpiration rate, stomatal conductance, and intercellular to ambient CO2 concentration. Strawberry leaves were collected at the end of the experiment to analyze the antioxidant response. The highest antifungal activity both in vitro and on strawberries had coriander seed essential oil, which decreased grey mold severity. Coriander extract increased the photosynthetic capacity and antioxidant response of strawberry plants, however had negative effect on suppression of grey mold. In most cases, the essential oil activated antioxidant response of strawberry plants lower than extract. Our study results provide no direct impact of increased photosynthetic capacity values and antifungal effect after treatment with natural oils. The highest concentrations of coriander essential oil and extract potentially demonstrated a phytotoxic effect.